The submersion of Pedilanthus into Euphorbia (Euphorbiaceae) - Steinmann, Victor W. (Instituto de Ecología, A.C., 2003)
Pedilanthus (Euphorbiaceae) consists of about 15 species, all of which occur in Mexico. The genus belongs to the tribe Euphorbieae subtribe Euphorbiinae in the subfamily Euphorbioideae, and is one of six satellite genera of Euphorbia. As traditionally suspected, molecular studies have demonstrated that Euphorbia is paraphyletic, and the satellite genera are nested within it. In order to create a classification of Euphorbieae subtribe Euphorbiinae that reflects evolutionary relationships and employs the concept of monophyly, I argue that the genera currently segregated from Euphorbia should be included within it. Therefore, Pedilanthus is here treated as a synonym of Euphorbia. A list enumerating the valid names for species of Pedilanthus when treated within Euphorbia is provided. The following new combinations and names are proposed: Euphorbia calcarata, Euphorbia coalcomanensis, Euphorbia colligata, Euphorbia conzattii, Euphorbia cymbifera, Euphorbia cyri, Euphorbia diazlunana, Euphorbia dressleri, Euphorbia finkii, Euphorbia lomelii, Euphorbia peritropoides, Euphorbia personata, Euphorbia tehuacana, and Euphorbia tithymaloides sspp. angustifolia, bahamensis, jamaicensis, padifolia, parasitica, retusa, and smallii.